Financial Literacy: The Key to Successful Family Financial Management - Sihaloho, Fahmi Ashari S. (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2023)
The family is the smallest unit of a society. The family is a unit consisting of the head of the household and several people who gather and live in one place under one roof in a state of mutual dependence on one another. Financial problems are something that must be experienced by a family, especially families who are just starting the household ark. Therefore, it is necessary to have good financial literacy so that family finances can be managed properly in order to achieve family welfare. The method used in this paper is literature study from journals and books and other publications related to the variables in this paper. The data in this study were taken from books and journal articles which were combined to provide solutions and procedures for good family financial management. This paper discusses how to do good financial planning so that families can adjust their expenses to family income. It is hoped that this paper can reduce the negative impact of public ignorance about family financial management